NS3-based training system for learning RIPng for IPv6 (2017)
(Eng) This article shows the implementation of simulation software which aims to facilitate learning the RIPng protocol (for IPv6). This is based on an IPv6 network with loop topology, on which it is possible to program the tear down moment for one of the least-cost links; said link has been previously used in the routing table calculations which were operating before the tear down. Simulation includes three options which allow the user to choose the control strategy which helps avoiding routing loops: PoisonReverse, SplitHorizon and NoSplitHorizon. The software was developed under the programming environment of the NS-3 network simulator.